The role of transformational leadership and innovation adoption in restaurant performance - dos Anjos, Sara Joana Gadotti (2024)
The objective was to analyse the innovation influenced by transformational leadership in restaurant industry performance. The online questionnaire was applied via Amazon Mechanical Turk. Data collection reached 254 restaurant sector professionals, and their responses were analysed using descriptive statistics, correlation, and multiple regression. The results indicated that the innovation dimensions (menu, experiential, promotion, and technology) correlate positively and highly with transformational leadership. Innovations' impact and predictive power on restaurant performance were assessed, with leadership level as a weighting. The innovations related to the menu have the highest positive impact, followed by the innovations in promotion and experience. However, the innovation in technology had no significant impact. The result of the study provides theoretical and empirical contributions to the restaurant industry, generating propositions of innovative actions and highlighting the importance of transformational leadership. In the end, innovation is a critical part of any strategy to strengthen competitiveness and must be actively managed by leadership, stimulating the generation of new ideas and their conversion into marketable solutions.